2019
DOI: 10.1016/j.scitotenv.2019.04.157
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent effects of polystyrene nanoparticles in brine shrimp Artemia franciscana at physiological, biochemical and molecular levels

Abstract: Micro-( 5 mm) and nanoplastics ( 1 μm) are emerging threats for marine ecosystems worldwide. Brine shrimp Artemia is recognized as a suitable model among planktonic species for studying the impact of polystyrene nanoparticles (PS NPs) through short and long-term bioassays. Our study aims to evaluate the timedependent effects of cationic amino-modified PS-NH 2 (50 nm) in A. franciscana after short-(48 h) and long-term exposure (14 days). For this purpose, nauplii were exposed to a concentration range of PS-NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 57 publications
(79 reference statements)
10
68
0
1
Order By: Relevance
“…For example, different batches of PS-NH 2 NPs (50 nm) from the Bangs Laboratories Inc., kept an average hydrodynamic size ranging from 58 to 196 nm in different NSW media from the Mediterranean region (Della Torre et al, 2014;Bergami et al, 2016Bergami et al, , 2017Manfra et al, 2017;Pinsino et al, 2017;Marques-Santos et al, 2018;Grassi et al, 2019), thus showing no or slight agglomeration soon after dispersion. However, timeresolved DLS measurements revealed a strong agglomeration behavior of PS-NH 2 in NSW after 48 and 72 h, with large aggregates up to 5 µm, which were more prone to sedimentation (Varó et al, 2019).…”
Section: Ps Np Behavior In Seawater Mediamentioning
confidence: 91%
See 1 more Smart Citation
“…For example, different batches of PS-NH 2 NPs (50 nm) from the Bangs Laboratories Inc., kept an average hydrodynamic size ranging from 58 to 196 nm in different NSW media from the Mediterranean region (Della Torre et al, 2014;Bergami et al, 2016Bergami et al, , 2017Manfra et al, 2017;Pinsino et al, 2017;Marques-Santos et al, 2018;Grassi et al, 2019), thus showing no or slight agglomeration soon after dispersion. However, timeresolved DLS measurements revealed a strong agglomeration behavior of PS-NH 2 in NSW after 48 and 72 h, with large aggregates up to 5 µm, which were more prone to sedimentation (Varó et al, 2019).…”
Section: Ps Np Behavior In Seawater Mediamentioning
confidence: 91%
“…In Artemia spp. PS-NH 2 NPs provoked significant physiological alterations in the exposed larvae, including multiple molting (Bergami et al, 2016(Bergami et al, , 2017 as well as oxidative stress and neurotoxicity over short-and long-term exposure, as indicated by the significant decrease in the cholinesterase activity (Varó et al, 2019), leading to mortality after 14 days (Bergami et al, 2017;Varó et al, 2019). Long-term endpoints appeared thus more suitable to assess the toxicity of PS NPs to marine zooplankton (Lee et al, 2013;Bergami et al, 2017;Varó et al, 2019).…”
Section: Effects On Marine Organismsmentioning
confidence: 99%
“…Recently a study with the estuarine crustacean Artemia franciscana exposed to microplastics revealed that CE activity (using pNPA for the measurements) was inhibited (Varo et al, 2019). However, the authors were unable to relate if the toxicity was due to the polymer itself or to its additives.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…organotin compounds, inducing imposex), a long-lasting concern in the Mediterranean (Anastasiou et al, 2016;Sole et al, 1998). CEs in marine crustaceans have also been targeted as biomarkers of chemical exposure (Anto et al, 2009;Sole et al, 2009;Varo et al, 2019). In the later, the juvenile hormone methyl farnesoate is J o u r n a l P r e -p r o o f metabolised by a particular type of CE.…”
Section: Introductionmentioning
confidence: 99%
“…暴露时间也是影响生物毒性大小的重要因素. Feng 等 [19] 发现以取代酚、农药、离子液体为组分的六元混合 物对秀丽线虫致死毒性具有明显的时间依赖协同效应, 暴露 24 h 后的混合物毒性明显大于 12 h. Varo 等 [38] 发现 短期暴露时纳米塑料对卤虫无明显毒性, 但长期暴露会 导致生长受损. 根据青海弧菌的生长曲线, 常常采用暴 露 0.25 h 和 12 h 为急 性 毒 性 与慢 性 毒 性 观测时 间 [22,29,39] .…”
Section: 引言unclassified